2016
DOI: 10.18203/2349-3933.ijam20163724
|View full text |Cite
|
Sign up to set email alerts
|

A study of the sociodemographic, clinical, pathological and radiological profile of lung cancer in a tertiary care center

Abstract: Background: Lung cancer now constitutes the majority of all cancer diagnosis in the world. It has the most unfavourable prognosis accounting for the maximum number of cancer related deaths worldwide. The objective of this study was to study the complete profile of lung cancer. Prevalence of EGFR mutation in adenocarcinoma. Methods: 116 lung cancer patients were enrolled. They were subjected to diagnostic procedures like transthoracic FNAC/biopsy, bronchoscopy, thoracoscopy, closed pleural biopsy, lymph node FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In regard to occupation, about one third of the patients were farmers and labourers respectively. Study done by Kshetrimayum S et al 12 confirms the similar trend.…”
Section: Resultssupporting
confidence: 61%
“…In regard to occupation, about one third of the patients were farmers and labourers respectively. Study done by Kshetrimayum S et al 12 confirms the similar trend.…”
Section: Resultssupporting
confidence: 61%
“…However, this ratio was 1.7:1 to 3.9:1 in different Indian studies. 15,16 In our county, women have a lesser frequency of smoking and less pollution exposure than males. In average smoker men, the chance of developing bronchial carcinoma is nearly nine to ten times higher than in nonsmokers whereas the risk increased at least 20-fold in the case of heavy smokers.…”
Section: Resultsmentioning
confidence: 89%
“…A study done by Kshetrimayum et al in Lucknow showed a similar drastic difference between male and female smokers in India. [19] However, Western studies show that an increasing trend of female smokers is resulting in identical risk between men and women [2].…”
Section: Discussionmentioning
confidence: 99%
“…International studies [19,22,23,24] showed cough and breathlessness to be the most common presentations followed by chest pain and weight loss. This showed a similar pattern of symptoms in our study compared with other studies.…”
mentioning
confidence: 99%